Pengaruh Produk Halal terhadap Pilihan Konsumen dalam Berbelanja di Indonesia - Dewi, Meirita Sita; Cuandra, Fendy (SAFE-Network, 2023)
Halal is an essential factor for Muslim consumers in choosing products and services. Indonesia is a country with the largest Muslim population in the world. Producers must understand the factors that influence consumer buying behavior towards halal products. Sales of halal products are increasing, especially demand from Muslim consumers. This study aims to determine consumer buying behavior when buying halal products in Indonesia. This study involves the variables of halal awareness, halal logo, attitude, halal marketing, and halal image as independent variables, and buying behavior as the dependent variable. This study uses quantitative research methodology. The research data used primary data. Primary data was collected through a survey using a structured questionnaire. The questionnaire was created using Google Forms and distributed online to respondents. The data collection technique uses a probability sampling technique. The samples are selected randomly. The sample data was 320 respondents. The data analysis method uses SEM (Structural Equation Modeling) to predict the effect of independent variables on the dependent variable. The results of this study indicate that halal attitudes and images influence consumer behavior when buying halal products. Halal awareness, halal logo, and halal marketing do not influence consumer buying behavior when buying halal products. The findings of this study have implications for marketers and manufacturers in developing marketing strategies for halal products in Indonesia. Marketers need to understand the needs and preferences of Muslim consumers by building a positive attitude and halal image on the products sold. The availability of halal products in the market can help drive more buying behavior toward halal products.